Overestimated cytotoxicity and underestimated whitening efficacy of glabridin: A result of its poor solubility in DMSO - Liu, Haiyan; Wang, Anning; Chen, Xiaoyi; Hou, Sen; Li, Anzhang (PloS one, 2025)
Glabridin is widely used as a whitening agent in cosmetics, but its cytotoxicity remains a key concern in safety evaluations. In typical cytotoxicity assays, glabridin is dissolved in dimethyl sulfoxide (DMSO) before being added to the cell culture medium because it is insoluble in water. However, our study revealed that when the DMSO solution of glabridin was mixed with cell culture medium, glabridin was rapidly released due to its poor solubility in the DMSO/water mixture. The released glabridin rapidly formed crystals, which failed to enter cells. Consequently, the whitening efficacy of glabridin was reduced. Moreover, the glabridin crystals produced higher cytotoxicity, possibly due to the physical damage caused by their sharp crystalline structures. However, encapsulating glabridin in cyclodextrin (CD) can address these challenges, offering a better approach for glabridin cytotoxicity assays. The CD encapsulation method, compared to the DMSO solution method, not only decreased the cytotoxicity of glabridin but also increased its whitening efficacy. By comparing the efficacy of glabridin dissolved in DMSO and encapsulated in CD, we discovered that the reported cytotoxicity of glabridin may have been overestimated in previous cytotoxicity studies which used DMSO as a solvent, while its whitening efficacy may have been underestimated. These findings not only offer new insights for in vitro studies of glabridin-like reagents, but also facilitate the development of safer and more effective whitening products.